(untitled) (Vietnam Journal of Community Medicine, 2025)
Background: Acute colonic pseudo-obstruction or Ogilvie’s syndrome, is a rare condition characterized by significant colonic dilatation without mechanical obstruction. It is commonly observed in patients with multiple comorbidities, trauma, or postoperative status. Diagnosis and treatment remain clinical challenges, as delayed diagnosis and inappropriate management can lead to colonic ischemia or perforation. Objective: To present a clinical case of Ogilvie’s syndrome, emphasizing the importance of early recognition and appropriate intervention to prevent complications. Case presentation: A 72-year-old male patient with a history of Parkinson’s disease, type 2 diabetes mellitus, and left nephrectomy for renal tumor (5 years prior) presented with episodic abdominal pain, abdominal distension, and obstipation. Despite initial conservative treatment in an internal medicine department, his condition did not improve. On the 8th day of illness, he was admitted to the emergency department of 108 Military Central Hospital with nausea, vomiting, obstipation, severe electrolyte imbalance, abdominal pain, marked distension, and prominent bowel loops. An abdominal X-ray showed significant colonic dilatation, while an abdominal CT scan revealed generalized colonic dilatation, and the findings suggested sigmoid volvulus. The patient underwent emergency surgery, where intraoperative findings confirmed diffuse colonic dilatation without clear evidence of mechanical obstruction at the sigmoid colon. Postoperative diagnosis consisted of Ogilvie’s syndrome. Conclusion: Ogilvie’s syndrome is a rare but potentially fatal condition with a relatively high mortality rate. Early management, including conservative measures and decompression via colonoscopy, is crucial. Rapid colonic distension can lead to perforation and generalized peritonitis, necessitating timely surgical intervention. Prompt diagnosis and appropriate treatment play a critical role in reducing complications and mortality.